Research of synthetic iron microstructure parameters to maximize of its quality - Коваль, Оксана Сергеевна (Technology audit and production reserves, 2014)
The analysis of existing quality system in foundry is given in the article. One of the main components of product yield quality is the influence of chemical composition of the alloy on mechanical properties and microstructure parameters. It is proposed the methods of microstructure evaluation using mathematical methods: least squares and normal distribution law. Graphite is selected as quality criterion for research. The diagrams of graphite distribution in cast iron are constructed as a result of microstructure analyses. This will allow to create a mathematical model of chemical composition influence of input parameters on the output parameters in the smelting of cast iron. This is an actual problem in real production. Researches in this area will reduce the probability of defective items and improve the physical and mechanical properties of molded pieces.